Two-dimensional fracture modeling with the generalized/extended finite element method: An object-oriented programming approach. (January 2018) - Malekan, Mohammad; Silva, Leandro L.; Barros, Felicio B.; Pitangueira, Roque L.S.; Penna, Samuel S.
Highlights: A new computational framework for crack nucleation and propagation that covers both linear and nonlinear material models, using the Generalized/Extended Finite Element Method (G/XFEM). Detailed implementation based on Object-oriented programming approach. Results from the plane stress and Reissner-Mindlin plate numerical experiments are presented considering both linear and nonlinear material models. A straight forward implementation to add additional linear/nonlinear solvers and also different enrichment types to tackle new types of mechanical problems. Abstract: This work presents an object-oriented implementation of the G/XFEM to model the crack nucleation and propagation in structures made of either linear or nonlinear materials. A discontinuous function along with the asymptotic crack-tip displacement fields are used to represent the crack without explicitly meshing its surfaces. Different approach are explained in detail that are used to capture the crack nucleation within the model and also determine the crack propagation path for various problems. Stress intensity factor and singularity of the localization tensor (which provides the classical strain localization condition) can be used to determine the crack propagation direction for linear elastic materials and nonlinear material models, respectively. For nonlinear material model, the cohesive forces acting on the crack plane are simulated in the enrichment process by incorporating a discrete constitutive model. Several algorithms and strategies have been implemented, within an object-oriented framework in Java, called INSANE. This implementation will be presented in detail by solving different two-dimensional problems, for both linear and nonlinear material models, in order to show the robustness and accuracy of the proposed method. The numerical results are compared with the reference solutions from the analytical, numerical or experimental results, where applicable.